ENGINE 5 FUEL RATIO OPTIMIZATION WITH LOAD FEEDBACK CORRECTION USING VAMPSET SOFTWARE TO REDUCE SPECIFIC GAS CONSUMPTION (SGC) AT PT PLN NUSANTARA POWER ARUN GENERATION UNIT - Yusrizal, Y; Zulkifli, Z; Rihayat, R (Politeknik Negeri Lhokseumawe, 2024)
ABSTRACTFuel Ratio Optimization with 3% Load Feedback Correction to Reduce Specific Gas Consumption (SGC) at PLTMG Arun is a test in the field of power plants that focuses on optimizing the SGC Engine of PLTMG by looking for a fuel mixture composition that produces optimal efficiency of the generating engine and is safe for the reliability of the plant. In 2023, the SGC target is 8600 BTU/kWh. The highest SGC value of one of the engines in 2023 is in Engine 5 of 9327.27 BTU/kWh with an average exhaust gas temperature of 528°C, while the lowest SGC value in Engine 10 is 8,481 BTU/kWh with an average exhaust gas temperature of 532°C. The difference in exhaust gas temperature shows that there is an unused potential for heat energy in engine 5, causing a significant difference in SGC. This test aims to optimize the combustion point using a structured method calculation reference, maintain the engine exhaust gas temperature in accordance with the commissioning limits, lower the SGC and increase efficiency, then it will be obtained as a reference as the basis for changes from the AFR. For AFR tuning from the initial condition, i.e. load feedback = load output generator, it will then be converted to load feedback load output generator. The method used is to use the load feedback correction method by modifying the analog value scale of the output of the Power Monitoring Unit (PMU) from the initial condition of 4-20 mA = 0-12000 kW to the modified condition of 4-20 mA = (0-(12000+x%) kW, where this condition adjusts from the allowable combustion results according to the lean burn diagram from the manufacturer. From the implementation in October 2023, the SGC value decreased from the previous 9327.27 BTU/kWh to 9177.87 BTU/kWh. In addition, there was an increase in plant efficiency from 36.54% to 37.14, an increase in EAF from 98.34% to 98.91%, a decrease in EFOR from 1.37% to 0.09% and a decrease in GPHR from 2350,473 Kcal/KWh to 2312,673 Kcal/KWh.keyword: Engine, fuel ratio, specific gas consumption, commissioning, load feedback, efisiensi, exhaust gas temperature.